The Attentional Control of Younger and Older Adults in Forced-Attention Dichotic Listening of Cantonese Tones. - Wang, Yuqi; Yang, Xiaohu; Qin, Quentin Zhen (Journal of Speech, Language & Hearing Research, 2026)
Purpose: The forced-attention dichotic listening (FADL) task is used to examine how people control attention during speech processing. Younger adults can flexibly shift attention to instructed ears from the baseline right-ear advantage (REA) for consonants (cued by temporal information). However, it remains underexplored whether tonal language speakers can control their attention to tones, which are cued by spectral information and typically trigger a left-ear advantage (LEA) at baseline. Moreover, older adults sometimes fail to show these patterns, as compared to younger adults, possibly due to age-related decline. This study investigated whether these attentional controls generalize to Cantonese tones and whether younger and older Cantonese speakers show different attentional control in an FADL task of Cantonese tones. Method: Sixty native Cantonese-speaking younger adults, aged 18-25 years (Experiment 1), and 64 older adults, aged 59-72 years (Experiment 2), completed tone training followed by an FADL test. In three conditions (i.e., nonforced, forced-left [FL], and forced-right [FR]), they identified dichotically presented Cantonese tones according to attentional instructions. Results: Both the younger and older adults successfully modulated attention. The participants, regardless of age, enhanced the LEA in the FL condition and reversed it to an REA in the FR condition. An exploratory group comparison showed that younger adults might exhibit a significantly larger shift of ear preference in the FL condition than older adults. Conclusions: The findings provide evidence that auditory attentional control is a highly flexible and cue-general cognitive function, which can be generalized to Cantonese tones. Crucially, the core performance of attentional control in Cantonese processing remains largely preserved with aging. It suggests that age-related decline is not the only consequence of aging, but compensatory strategies are adopted by older adults to cope with possible decline and keep their behavioral performance intact.